An Analytical Study of the Leadership Traits among Referees of Team Sports in Jordan - Taha, Manal Mohammed; Gharagheer, Ahmed Shaher (Dirasat: Educational Sciences, 2023)
Objectives: The study aimed to assess leadership traits among Jordanian team sports referees and examine variations based on study variables: sport type, refereeing level, experience, and gender. Methods: The study employed a descriptive approach and included a sample of 227 team sports referees across all levels, registered with sports federations during the 2020/2021 season. The questionnaire contained 44 items categorized into five domains: social, mental, emotional, personal, and decision-making traits. Responses were classified as high (3.667-5.000), medium (2.334-3.666), or low (1-2.333). Statistical analysis included means, standard deviations, multidirectional analysis of variance, and Cronbach's alpha. Results: The study revealed that Jordanian team sports referees displayed a high level of distinguished leadership traits overall, with an average score of 4.45. Across the five domains studied, mental and cognitive characteristics ranked highest (4.53), followed by personal and physical traits (4.51), social traits (4.50), sentimental and emotional traits (4.43), and decision-making traits (4.24). Additionally, the results indicated no statistically significant differences (α ≥ 0.05) in leadership traits based on study variables, including sport type, refereeing level, years of experience, and gender. Conclusions: The study concluded that the referees of team games in Jordan (football, basketball, handball, volleyball) are characterized by leadership traits to a high degree.The study recommended to conduct studies to determine the characteristics of referees from the players and coaches point of view.